Study of orbital relocation of objects in GEO via orbital perturbations and solar sail - Brejão, L. F.; Prado, A. F.B.A.; Carvalho, J. P.S.; Mourão, D. C. [UNESP] (Springer Nature, 2023)
This study considers the use of solar sails as devices on board space vehicles to promote their orbital relocation after the end of the useful life of the object. It is considered a special vehicle in the geostationary orbital regime (GEO) subject to disturbances due to the gravitational potential of the Earth in zonal terms up to the sixth degree and in sectorial terms of degree and order two, in which the rotation of the Earth is implemented. In addition, the model of this study takes into account disturbances due to third bodies (Moon and Sun), and the direct solar radiation pressure, assuming a heliosynchronous sail, to extract the greatest possible solar effect. As an additional study, the lunisolar terrestrial tide effect is considered, according to Kozai’s model. It was found that a solar sail with an area-mass ratio of 10 m2/kg allows the debris to move away from the GEO region, meeting the IADC recommendations, over a period of approximately 14.5 years.